2016
DOI: 10.1111/trf.13700
|View full text |Cite
|
Sign up to set email alerts
|

Low transfusion transmission of hepatitis E among 25,637 single‐donation, nucleic acid‐tested blood donors

Abstract: Despite an HEV RNA prevalence of 0.04% in Danish blood donations, all HEV-positive donations carried low viral loads, and no evidence of TTI was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 34 publications
2
30
1
Order By: Relevance
“…The prevalence of HEV RNA positive donations was 1:2,331 (0.04%) [16], consistent with data from other northern European countries (Table). Positive donations had a median viral load of 13 IU/mL in a range from unquantifiable to 920 IU/mL [16]. Look-back studies of living recipients found no evidence of TT HEV infections [16].…”
Section: Hepatitis E Virus and Blood Donations In Selected European Csupporting
confidence: 85%
See 1 more Smart Citation
“…The prevalence of HEV RNA positive donations was 1:2,331 (0.04%) [16], consistent with data from other northern European countries (Table). Positive donations had a median viral load of 13 IU/mL in a range from unquantifiable to 920 IU/mL [16]. Look-back studies of living recipients found no evidence of TT HEV infections [16].…”
Section: Hepatitis E Virus and Blood Donations In Selected European Csupporting
confidence: 85%
“…Positive donations had a median viral load of 13 IU/mL in a range from unquantifiable to 920 IU/mL [16]. Look-back studies of living recipients found no evidence of TT HEV infections [16]. Based on these data, the Danish Society of Clinical Immunology does not recommend the screening of blood donations for HEV in Denmark [17].…”
Section: Hepatitis E Virus and Blood Donations In Selected European Cmentioning
confidence: 99%
“…It may also affect the virus ability to transmit and cause infection, since the pORF3 has been shown to be important for viral egress. This might mean that there is lower risk for hepatitis E transmission during the viraemic, although a seronegative state supports a study from Denmark [13]. Seroconversion to anti-HEV may occur after reversion of the ORF3 start codon to AUG.…”
Section: ---------L -----------------------Rp-----v----------------supporting
confidence: 56%
“…It has been shown that blood donors with HEV RNA may be anti-HEV negative for up to 48 days, before seroconversion [8,11]. There are studies showing a low risk of transmission of HEV from HEV RNA-positive blood donations [13], but also that it is cost effective to screen blood products for HEV to minimize hepatitis E posttransfusion [14]. Five European countries have introduced HEV RNA screening of blood products based on this [15].…”
mentioning
confidence: 99%
“…commun.]. Both Denmark and Sweden have evaluated the incidence of HEV-RNA in their blood donors and do not plan to implement HEV screening [22-24]. In Denmark, TT-HEV was not reported in recipients who received blood components from HEV-infected donors with low VL [22].…”
Section: Overview Of Eu Blood Donor Screening Methods and Strategiesmentioning
confidence: 99%